Boron nitride-based multi-shell wave-absorbing anticorrosive coating and preparation method thereof
Through the preparation method of boron nitride-based multi-shell absorbing anticorrosion coating, magnetically modified BN, multi-layer Fe-Co doped carbon shell and high-density modified TiO2 coating are used to solve the shortcomings of the existing coating in electromagnetic wave absorption and corrosion resistance, and achieve efficient electromagnetic wave absorption and multiple scattering, and improve corrosion resistance and chemical stability.
Patent Information
- Application Number
- CN202411983171.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
现有金属表面防护涂层在实现高效电磁波吸收与长期防腐性能方面存在不足,难以满足现代工业对高性能、多功能且环境友好的涂层防护体系的需求。
Using the preparation method of boron nitride-based multi-shell absorbing anticorrosion coating, a coating with multi-layer barrier and excellent weather resistance and anti-aging properties is constructed by coatings of magnetically modified BN, multi-layer Fe-Co doped carbon shells and high-density modified TiO2.
It realizes efficient electromagnetic wave absorption and multiple scattering, improves the anti-corrosion performance and physical strength of the coating, enhances chemical stability and anti-aging performance, and is suitable for the fields of wave absorption stealth, anti-corrosion protection and electromagnetic compatibility.
Smart Images

Figure CN119684876A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation methods of metal surface protective coatings, and specifically relates to a preparation method of a boron nitride-based multi-shell absorbing anti-corrosion coating, and also relates to an anti-corrosion coating prepared by the preparation method. Background Art
[0002] In the field of metal surface coating protection, with the continuous advancement of industrial technology and the widespread application of metal materials in various extreme environments, the requirements for the protection of metal surfaces are increasing. As the cornerstone of industrial production, the stability and durability of the performance of metal materials are crucial. However, when these materials are placed in harsh environmental conditions such as humidity, high temperature, and strong corrosiveness for a long time, they are extremely susceptible to multiple damages such as oxidation and corrosion. In addition, in places with intensive electromagnetic radiation, metal parts may also become the source or victim of electromagnetic interference, affecting the normal operation of equipment and the quality of communication. These problems not only seriously shorten the service life of metal parts and increase maintenance costs, but may also cause safety accidents, bring significant economic losses to enterprises, and even threaten people's lives and property.
[0003] Traditional metal surface protection methods, such as electroplating, thermal spraying and hot-dip plating, can enhance the corrosion resistance of metals to a certain extent, but they generally have defects such as complicated processes, serious environmental pollution, insufficient bonding strength between the coating and the metal substrate, and single function. Faced with increasingly complex and changeable corrosion environments and growing electromagnetic compatibility requirements, these traditional technologies can no longer meet the urgent needs of modern industry for high-performance, multifunctional and environmentally friendly coating protection systems. What is particularly critical is that with the rapid development of materials science and engineering technology, the optimization design of coating structures has become increasingly important. An excellent coating structure can not only significantly improve the protective performance of the coating, but also achieve the integration of coating multifunctionality while maintaining economy and ease of construction, such as having multiple functions such as corrosion protection and wave absorption.
[0004] The Chinese patent "A method for preparing a conductive, microwave-absorbing and anti-corrosion coating based on Mxene" has a publication number of CN114854240A. During the mixing process of the composite filler, the agglomeration phenomenon between the components may lead to poor dispersion uniformity in the epoxy resin matrix, affecting the stability and uniformity of the overall performance of the coating; the Chinese patent "High elastic microwave-absorbing heavy-duty anti-corrosion nano coating" has a publication number of CN101280144A. Due to the addition of multiple nanomaterials and the lack of structural design, nanoparticles are prone to agglomeration during the coating preparation process, making it difficult for the components to be evenly dispersed in the resin system, thereby affecting the consistency and stability of the coating performance; the Chinese patent "A phenolic epoxy anti-corrosion coating and its preparation method and application" has a publication number of CN119161789A. The coating performance is not comprehensive enough and cannot adapt to extreme environments such as metal surface protection under high electromagnetic radiation. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a boron nitride-based multi-shell absorbing and anti-corrosion coating, which solves the problem that the existing coatings are insufficient in achieving efficient electromagnetic wave absorption and long-term anti-corrosion performance.
[0006] Another object of the present invention is to provide an anti-corrosion coating prepared by a method for preparing a boron nitride-based multi-shell absorbing anti-corrosion coating.
[0007] The technical solution adopted by the present invention is a method for preparing a boron nitride-based multi-shell absorbing and anti-corrosion coating, specifically: first prepare magnetic modified BN, then prepare a multi-shell m-BN@Fe-Co microsphere precursor, and calcine it, then coat it with modified nano-TiO2, and finally prepare the absorbing and anti-corrosion coating.
[0008] The present invention is also characterized in that: The preparation method of the boron nitride-based multi-shell absorbing and anti-corrosion coating is specifically implemented according to the following steps: Step 1: Preparation of magnetically modified BN BN powder was added into a mixed solution of anhydrous ethanol and deionized water, and then FeSO4·7H2O, FeCl3·6 H2O and NaOH solution were added. After reacting in a water bath, the mixture was filtered, washed with water and dried to obtain magnetically modified BN particles. Step 2: Preparation of multi-shell m-BN@Fe-Co microsphere precursor The magnetically modified BN particles obtained in step 1 are added to a water-soluble polymer solution, filtered, washed and dried after hydrothermal treatment, and then dispersed in a FeCl3·6H2O solution, heated and stirred, filtered and dried, and then dispersed in a C4H6CoO4·4H2O solution, heated and stirred, filtered and dried to obtain a multi-shell m-BN@Fe-Co microsphere precursor; Step 3, calcination The multi-shell m-BN@Fe-Co microsphere precursor obtained in step 2 is calcined to obtain multi-shell m-BN@Fe-Co microspheres; Step 4: Modified nano-TiO2 coating The m-BN@Fe-Co microspheres, nano-TiO2 and dispersant obtained in step 3 are dispersed in deionized water, a dilute hydrochloric acid solution is added to adjust the pH, a surfactant is added, and the mixture is heated, stirred, dried and ground to obtain m-BN@Fe-Co@TiO2 nanospheres; Step 5: Prepare the microwave-absorbing and anti-corrosion coating The m-BN@Fe-Co@TiO2 nanospheres obtained in step 4 are mixed with epoxy resin, stirred evenly and then dispersed by ultrasonic, a curing agent is added, stirred evenly and then applied on an aluminum plate, and after being completely cured, a microwave-absorbing and anti-corrosion coating is obtained.
[0009] In step 1, the concentration of BN powder in the mixed solution of anhydrous ethanol and deionized water is 0.03 g / mL~0.05 g / mL, the volume ratio of anhydrous ethanol to deionized water is 1:2, the mass ratio of FeSO4·7H2O, FeCl3·6H2O and BN is 2:1:3~5:1:3, NaOH solution is added until the pH reaches 10~12, the water bath temperature is 40℃~70℃, and the reaction time is 1h~3h.
[0010] In step 2, the mass ratio of m-BN to the water-soluble polymer is 1:2~2:1, the hydrothermal temperature is 120°C~180°C, the hydrothermal time is 4h~8h, and the water-soluble polymer solution is any one of polyvinyl alcohol, polyacrylic acid, polycarbonate, chitosan, glucose, and polyacrylamide dissolved in deionized water, and its concentration in deionized water is 0.05g / mL~0.1g / mL.
[0011] In step 2, the FeCl3·6H2O solution and the C4H6CoO4·4H2O solution are respectively a mixed solution of FeCl3·6H2O dissolved in deionized water and anhydrous ethanol, and a mixed solution of C4H6CoO4·4H2O dissolved in deionized water and anhydrous ethanol. The concentrations of FeCl3·6H2O and C4H6CoO4·4H2O in the deionized water-anhydrous ethanol mixed solution are both 0.015 g / mL~0.05 g / mL, the mass ratio of m-BN to FeCl3·6H2O and C4H6CoO4·4H2O is 1:1:1~1:2:2, the heating temperature is 40°C~60°C, the stirring time is 12h~24h, the drying temperature is 60°C~80°C, and the drying time is 6h~12h.
[0012] Step 3 is specifically as follows: calcining the multi-shell m-BN@Fe-Co microsphere precursor obtained in step 2 at 400°C to 600°C in an air furnace, with a heating rate of 3°C / min, and keeping the temperature for 1h to 4h.
[0013] In step 4, the dispersant is any one of sodium pyrophosphate, polyethylene glycol, sodium polyacrylate, and sodium tripolyphosphate, the surfactant is any one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polysorbate 80, and sodium dodecylbenzene sulfonate, the mass ratio of m-BN@Fe-Co microspheres, nano-TiO2, dispersant and surfactant is 20:20:1:2~20:40:1:2, the concentration of nano-TiO2 in deionized water is 0.005g / mL~0.015g / mL, the pH is adjusted to 4~6, and stirring is carried out at 40℃~60℃ for 2h~4h.
[0014] In step 5, the mass filling rate of m-BN@Fe-Co@TiO2 nanospheres in the epoxy resin is 10%~50%, the curing agent is any one of diethylenetriamine, fatty polyamine ethylenediamine, polyetherdiamine, diaminocyclohexane, and trimethylhexanediamine, and the mass filling rate of the curing agent in the epoxy resin is 2%~5%.
[0015] During stirring in step 5, the stirring speed of the stirrer is 600 rpm to 800 rpm, the stirring time is 20 min to 60 min, and the ultrasonic time is 10 min to 30 min. Another technical solution adopted by the present invention is to prepare the anti-corrosion coating by adopting the preparation method of boron nitride-based multi-shell absorbing anti-corrosion coating.
[0016] The beneficial effects of the present invention are: The preparation method of the boron nitride-based multi-shell absorbing anti-corrosion coating of the present invention can obtain a high-density TiO2-coated absorbing anti-corrosion coating with multiple Fe-Co doped carbon shells and magnetically modified BN particle cores. The BN particles enhance their interaction with electromagnetic waves through magnetic modification, and the multi-layer Fe-Co doped carbon shells increase the absorbing mechanism and realize multiple scattering of electromagnetic waves, thereby improving the absorbing efficiency. The high-density coating of the outer modified nano-TiO2 enhances the interface polarization through its unique electronic structure and optimizes the absorbing effect. The multi-shell m-BN@Fe-Co microsphere design forms a multi-level barrier to effectively block corrosive media. The magnetically modified BN enhances the physical strength of the coating and repels corrosive ions, thereby improving the corrosion resistance. The outer high-density modified TiO2 enhances chemical stability, and further enhances the anti-corrosion effect through its excellent weather resistance and anti-aging properties. Therefore, the coating has broad application prospects in multiple key fields such as absorbing stealth, anti-corrosion protection and electromagnetic compatibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the microscopic morphology of m-BN@Fe-Co@TiO2 nanospheres prepared by the present invention. DETAILED DESCRIPTION
[0018] The present invention is described in detail below in conjunction with specific implementation modes and accompanying drawings.
[0019] The method for preparing the boron nitride-based multi-shell absorbing and anti-corrosion coating of the present invention is specifically implemented according to the following steps: Step 1: Preparation of magnetically modified BN BN powder was added into a mixed solution of anhydrous ethanol and deionized water, followed by the addition of FeSO4·7H2O, FeCl3·6 H2O and NaOH solution. After the reaction in a water bath, the mixture was filtered, washed with water and dried to obtain magnetically modified BN particles (m-BN). In step 1, the concentration of BN powder in the mixed solution of anhydrous ethanol and deionized water is 0.03 g / mL~0.05 g / mL, the volume ratio of anhydrous ethanol to deionized water is 1:2, the mass ratio of FeSO4·7H2O, FeCl3·6H2O and BN is 2:1:3~5:1:3, NaOH solution is added until the pH reaches 10~12, the water bath temperature is 40℃~70℃, and the reaction time is 1h~3h; Step 2: Preparation of multi-shell m-BN@Fe-Co microsphere precursor The m-BN obtained in step 1 is added to a water-soluble polymer solution, filtered, washed and dried after hydrothermal treatment, and then dispersed in a ferric chloride hexahydrate (FeCl3·6H2O) solution, heated and stirred, filtered and dried, and then dispersed in a cobalt acetate tetrahydrate (C4H6CoO4·4H2O) solution, heated and stirred, filtered and dried to obtain a multi-shell m-BN@Fe-Co microsphere precursor; In step 2, the mass ratio of m-BN to the water-soluble polymer is 1:2~2:1, the hydrothermal temperature is 120°C~180°C, the hydrothermal time is 4h~8h, and the water-soluble polymer solution is any one of polyvinyl alcohol, polyacrylic acid, polycarbonate, chitosan, glucose, and polyacrylamide dissolved in deionized water, and its concentration in deionized water is 0.05g / mL~0.1g / mL; In step 2, the FeCl3·6H2O solution and the C4H6CoO4·4H2O solution are respectively a mixed solution of FeCl3·6H2O dissolved in deionized water and anhydrous ethanol, and a mixed solution of C4H6CoO4·4H2O dissolved in deionized water and anhydrous ethanol, the concentrations of FeCl3·6H2O and C4H6CoO4·4H2O in the deionized water-anhydrous ethanol mixed solution (the volume ratio of deionized water to anhydrous ethanol is 1:1) are both 0.015 g / mL~0.05 g / mL, the mass ratio of m-BN to FeCl3·6H2O and C4H6CoO4·4H2O is 1:1:1~1:2:2, the heating temperature is 40°C~60°C, the stirring time is 12h~24h, the drying temperature is 60°C~80°C, and the drying time is 6h~12h; Step 3, calcination The multi-shell m-BN@Fe-Co microsphere precursor obtained in step 2 is calcined to obtain multi-shell m-BN@Fe-Co microspheres; Step 3 is specifically as follows: calcining the multi-shell m-BN@Fe-Co microsphere precursor obtained in step 2 at 400°C to 600°C in an air furnace at a heating rate of 3°C / min and keeping the temperature for 1h to 4h; Step 4: Modified nano-TiO2 coating The m-BN@Fe-Co microspheres, nano-TiO2 and dispersant obtained in step 3 are dispersed in deionized water, a dilute hydrochloric acid solution is added to adjust the pH, a surfactant is added, and the mixture is heated, stirred, dried and ground to obtain m-BN@Fe-Co@TiO2 nanospheres; In step 4, the dispersant is any one of sodium pyrophosphate, polyethylene glycol, sodium polyacrylate, and sodium tripolyphosphate, the surfactant is any one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polysorbate 80, and sodium dodecylbenzene sulfonate, the mass ratio of m-BN@Fe-Co microspheres, nano-TiO2, dispersant, and surfactant is 20:20:1:2-20:40:1:2, the concentration of nano-TiO2 in deionized water is 0.005 g / mL-0.015 g / mL, the pH is adjusted to 4-6, and stirred at 40°C-60°C for 2h-4h; Step 5: Prepare the microwave-absorbing and anti-corrosion coating The m-BN@Fe-Co@TiO2 nanospheres obtained in step 4 are mixed with epoxy resin, stirred evenly and then dispersed by ultrasonication, a curing agent is added, stirred evenly and then applied on an aluminum plate, and after being completely cured, a microwave absorbing and anti-corrosion coating is obtained; In step 5, the mass filling rate of m-BN@Fe-Co@TiO2 nanospheres in the epoxy resin is 10%~50%, the curing agent is any one of diethylenetriamine, fatty polyamine ethylenediamine, polyetherdiamine, diaminocyclohexane, and trimethylhexanediamine, and the mass filling rate of the curing agent in the epoxy resin is 2%~5%. During stirring, the stirrer speed is 600rpm~800rpm, the stirring time is 20min~60min, and the ultrasonic time is 10min~30min.
[0020] The present invention selects magnetic particles to modify BN to enhance its interaction with electromagnetic waves; adopts continuous template technology to control the content of metal ions in the carbon layer and their penetration depth by adjusting the concentration of the metal ion solution, thereby successfully constructing m-BN@Fe-Co microspheres with a multi-shell structure, which not only enriches the attenuation path of electromagnetic waves, realizes the multiple scattering effect of electromagnetic waves, enhances wave absorption, but also constructs a multi-level protective barrier to effectively block the invasion of corrosive media; controls the ratio of nano-TiO2, dispersant and surfactant to obtain high-density modified TiO2 coated on the surface of the m-BN@Fe-Co microspheres, enhances interface polarization, optimizes wave absorption, and further enhances the anti-corrosion effect through its excellent weather resistance and anti-aging properties.
[0021] Example 1 The preparation method of the boron nitride-based multi-shell absorbing and anti-corrosion coating of the present invention is specifically as follows: First, 0.9 g of BN powder was ultrasonically dispersed in a mixed solution of 10 mL of anhydrous ethanol and 20 mL of deionized water to obtain a BN suspension. Then, 0.6 g of FeSO4·7H2O and 0.3 g of FeCl3·6 H2O were added thereto, stirred evenly, and NaOH solution was added dropwise until the pH value was 10. The mixed solution was placed in a high-temperature reactor, reacted at 40 °C for 1 h, and then filtered. The mixture was washed with water several times and dried to obtain magnetically modified BN particles (m-BN). Weigh 1.5g of polyvinyl alcohol and dissolve it in 30mL of deionized water, then add 0.75g of m-BN, ultrasonically disperse it evenly, put it into a high-temperature reactor, react at 120℃ for 4h, filter it, wash it three times and dry it to obtain a black product. Weigh 0.75g of FeCl3·6H2O and dissolve it in a mixed solution of 25mL of deionized water and 25mL of anhydrous ethanol, add the black product, ultrasonically disperse it for 30min, and heat and stir it at 40℃ for 12h. Then filter the resulting mixture solution by suction, dry it at 60℃ for 6h to obtain the m-BN@Fe microsphere precursor. Weigh 0.75g of C4H6CoO4·4H2O and dissolve it in a mixed solution of 25mL of deionized water and 25mL of anhydrous ethanol, add the obtained m-BN@Fe microsphere precursor, ultrasonically disperse it for 30min, heat and stir it at 40℃ for 12h, filter it, and dry it at 60℃ for 6h to obtain the m-BN@Fe-Co microsphere precursor; The m-BN@Fe-Co microsphere precursor was placed in an air furnace with a heating rate of 3°C / min and kept at 400°C for 1 h to obtain multi-shell m-BN@Fe-Co microspheres. Add 1g of m-BN@Fe-Co microspheres, 1g of nano-TiO2 and 0.05g of sodium pyrophosphate to 200mL of deionized water, disperse by ultrasonic for 30min, add dilute hydrochloric acid to adjust the pH to 4, add 0.1g of sodium dodecyl sulfate, stir at 40℃ for 2h, dry and grind into powder to obtain m-BN@Fe-Co@TiO2 nanospheres; Weigh 1gm-BN@Fe-Co@TiO2 nanospheres and add them to 10g epoxy resin. Stir at 600rpm for 20min and then ultrasonically disperse for 10min. Add 0.2g diethylenetriamine, stir evenly and apply it on an aluminum plate. After complete curing, a radar-absorbing and anti-corrosion coating is obtained.
[0022] Example 2 The preparation method of the boron nitride-based multi-shell absorbing and anti-corrosion coating of the present invention is specifically as follows: First, 1.5g of BN powder was ultrasonically dispersed in a mixed solution of 10mL of anhydrous ethanol and 20mL of deionized water to obtain a BN suspension, and then 2.5g of FeSO4·7H2O and 0.5g of FeCl3·6 H2O were weighed and added, and NaOH solution was added dropwise until the pH value was 12 after stirring. The mixed solution was placed in a high-temperature reactor, reacted at 70°C for 3h, and then filtered, washed with water several times, and dried to obtain magnetically modified BN particles (m-BN); Weigh 3g of glucose and dissolve it in 30mL of deionized water, then add 6g of m-BN, ultrasonically disperse it evenly, put it into a high-temperature reactor, react at 180℃ for 8h, filter it, wash it three times and dry it to obtain a black product. Weigh 12g of FeCl3·6H2O and dissolve it in a mixed solution of 120mL of deionized water and 120mL of anhydrous ethanol, add the black product, ultrasonically disperse it for 30min, heat it at 60℃ and stir it for 24h. Then filter the resulting mixture solution by suction, dry it at 80℃ for 12h to obtain the m-BN@Fe microsphere precursor. Weigh 12g of C4H6CoO4·4H2O and dissolve it in a mixed solution of 120mL of deionized water and 120mL of anhydrous ethanol, add the obtained m-BN@Fe microsphere precursor, ultrasonically disperse it for 30min, heat it at 60℃ and stir it for 24h, filter it, and dry it at 80℃ for 12h to obtain the m-BN@Fe-Co microsphere precursor; The m-BN@Fe-Co microsphere precursor was placed in an air furnace with a heating rate of 3°C / min and kept at 600°C for 4 h to obtain multi-shell m-BN@Fe-Co microspheres. Add 1gm-BN@Fe-Co microspheres, 2g nano-TiO2 and 0.05g polyethylene glycol to 133mL deionized water, ultrasonically disperse for 30min, add dilute hydrochloric acid to adjust the pH to 6, add 0.1g hexadecyltrimethylammonium bromide, stir at 60℃ for 4h, dry, and grind into powder to obtain m-BN@Fe-Co@TiO2 nanospheres; Weigh 5 g of m-BN@Fe-Co@TiO2 nanospheres and add them to 10 g of epoxy resin. Stir at 800 rpm for 60 min and then ultrasonically disperse for 30 min. Add 0.5 g of aliphatic polyamine ethylenediamine, stir evenly and apply it on an aluminum plate. After complete curing, an absorbing and anti-corrosion coating is obtained.
[0023] Example 3 The preparation method of the boron nitride-based multi-shell absorbing and anti-corrosion coating of the present invention is specifically as follows: First, 1.2g of BN powder was ultrasonically dispersed in a mixed solution of 10mL of anhydrous ethanol and 20mL of deionized water to obtain a BN suspension, and then 1.5g of FeSO4·7H2O and 0.4g of FeCl3·6 H2O were added thereto, stirred evenly, and NaOH solution was added dropwise until the pH value was 11. The mixed solution was placed in a high-temperature reactor, reacted at 50°C for 2h, and then filtered, washed with water several times, and dried to obtain magnetically modified BN particles (m-BN); Weigh 2g of polyacrylic acid and dissolve it in 30mL of deionized water, then add 3g of m-BN, ultrasonically disperse it evenly, put it into a high-temperature reactor, react at 150℃ for 6h, filter it, wash it three times and dry it to obtain a black product. Weigh 5g of FeCl3·6H2O and dissolve it in a mixed solution of 125mL of deionized water and 125mL of anhydrous ethanol, add the black product, ultrasonically disperse it for 30min, heat it at 50℃ and stir it for 18h. Then filter the resulting mixture solution by suction, dry it at 70℃ for 10h to obtain the m-BN@Fe microsphere precursor. Weigh 5g of C4H6CoO4·4H2O and dissolve it in a mixed solution of 125mL of deionized water and 125mL of anhydrous ethanol, add the obtained m-BN@Fe microsphere precursor, ultrasonically disperse it for 30min, heat it at 50℃ and stir it for 18h, filter it, and dry it at 70℃ for 10h to obtain the m-BN@Fe-Co microsphere precursor; The m-BN@Fe-Co microsphere precursor was placed in an air furnace with a heating rate of 3°C / min and kept at 500°C for 3 h to obtain multi-shell m-BN@Fe-Co microspheres. Add 1gm-BN@Fe-Co microspheres, 1.5g nano-TiO2 and 0.05g sodium polyacrylate to 150mL deionized water, ultrasonically disperse for 30min, add dilute hydrochloric acid to adjust the pH to 5, add 0.1g polysorbate 80, stir at 50℃ for 3h, dry, and grind into powder to obtain m-BN@Fe-Co@TiO2 nanospheres; Weigh 3 g of m-BN@Fe-Co@TiO2 nanospheres and add them to 10 g of epoxy resin. Stir at 700 rpm for 40 min and then ultrasonically disperse for 20 min. Add 0.3 g of polyether diamine, stir evenly and apply it on an aluminum plate. After complete curing, an absorbing and anti-corrosion coating is obtained.
[0024] Example 4 The preparation method of the boron nitride-based multi-shell absorbing and anti-corrosion coating of the present invention is specifically as follows: First, 0.9 g of BN powder was ultrasonically dispersed in a mixed solution of 10 mL of anhydrous ethanol and 20 mL of deionized water to obtain a BN suspension, and then 1 g of FeSO4·7H2O and 0.4 g of FeCl3·6 H2O were added thereto, stirred evenly, and then NaOH solution was added dropwise until the pH value was 10. The mixed solution was placed in a high-temperature reactor, reacted at 50 ° C for 2 h, and then filtered, washed with water several times, and dried to obtain magnetically modified BN particles (m-BN); Weigh 1.5g chitosan and dissolve it in 30mL deionized water, then add 0.75g m-BN, ultrasonically disperse it evenly, put it into a high-temperature reactor, react at 120℃ for 4h, filter it, wash it three times and dry it to get a black product. Weigh 1g FeCl3·6H2O and dissolve it in a mixed solution of 12mL deionized water and 12mL anhydrous ethanol, add the black product, ultrasonically disperse it for 30min, heat and stir it at 40℃ for 12h. Then filter the resulting mixture solution by suction, dry it at 60℃ for 6h to get the m-BN@Fe microsphere precursor. Weigh 1g C4H6CoO4·4H2O and dissolve it in a mixed solution of 25mL deionized water and 25mL anhydrous ethanol, add the obtained m-BN@Fe microsphere precursor, ultrasonically disperse it for 30min, heat and stir it at 40℃ for 12h, filter it, and dry it at 60℃ for 6h to get the m-BN@Fe-Co microsphere precursor; The m-BN@Fe-Co microsphere precursor was placed in an air furnace with a heating rate of 3°C / min and kept at 500°C for 4 h to obtain multi-shell m-BN@Fe-Co microspheres. Add 1g of m-BN@Fe-Co microspheres, 1g of nano-TiO2 and 0.05g of sodium tripolyphosphate to 80mL of deionized water, disperse by ultrasonic for 30min, add dilute hydrochloric acid to adjust the pH to 4, add 0.1g of sodium dodecylbenzene sulfonate, stir at 40℃ for 2h, dry and grind into powder to obtain m-BN@Fe-Co@TiO2 nanospheres; Weigh 4 gm-BN@Fe-Co@TiO2 nanospheres and add them to 10 g epoxy resin. Stir at 700 rpm for 20 min and then ultrasonically disperse for 10 min. Add 0.5 g diaminocyclohexane, stir evenly and apply it on an aluminum plate. After complete curing, an absorbing and anti-corrosion coating is obtained.
[0025] Example 5 The preparation method of the boron nitride-based multi-shell absorbing and anti-corrosion coating of the present invention is specifically as follows: First, 0.9g of BN powder was ultrasonically dispersed in a mixed solution of 10mL of anhydrous ethanol and 20mL of deionized water to obtain a BN suspension, and then 1g of FeSO4·7H2O and 0.4g of FeCl3·6 H2O were added thereto, stirred evenly, and then NaOH solution was added dropwise until the pH was 12. The mixed solution was placed in a high-temperature reactor, reacted at 65°C for 2h, filtered, washed with water several times, and dried to obtain magnetically modified BN particles (m-BN); Weigh 1.5g chitosan and dissolve it in 30mL deionized water, then add 0.75g m-BN, ultrasonically disperse it evenly, put it into a high-temperature reactor, react at 120℃ for 4h, filter it, wash it three times and dry it to get a black product. Weigh 1g FeCl3·6H2O and dissolve it in a mixed solution of 12mL deionized water and 12mL anhydrous ethanol, add the black product, ultrasonically disperse it for 30min, heat and stir it at 40℃ for 12h. Then filter the resulting mixture solution by suction, dry it at 60℃ for 6h to get the m-BN@Fe microsphere precursor. Weigh 1g C4H6CoO4·4H2O and dissolve it in a mixed solution of 25mL deionized water and 25mL anhydrous ethanol, add the obtained m-BN@Fe microsphere precursor, ultrasonically disperse it for 30min, heat and stir it at 40℃ for 12h, filter it, and dry it at 60℃ for 6h to get the m-BN@Fe-Co microsphere precursor; The m-BN@Fe-Co microsphere precursor was placed in an air furnace with a heating rate of 3°C / min and kept at 600°C for 3 h to obtain multi-shell m-BN@Fe-Co microspheres. Add 1g of m-BN@Fe-Co microspheres, 1g of nano-TiO2 and 0.05g of sodium tripolyphosphate to 80mL of deionized water, disperse by ultrasonic for 30min, add dilute hydrochloric acid to adjust the pH to 4, add 0.1g of sodium dodecylbenzene sulfonate, stir at 40℃ for 2h, dry and grind into powder to obtain m-BN@Fe-Co@TiO2 nanospheres; Weigh 4 gm-BN@Fe-Co@TiO2 nanospheres and add them to 10 g epoxy resin. Stir at 800 rpm for 50 min and then ultrasonically disperse for 30 min. Add 0.5 g diaminocyclohexane, stir evenly and apply it on an aluminum plate. After complete curing, an absorbing and anti-corrosion coating is obtained.
[0026] Example 6 The preparation method of the boron nitride-based multi-shell absorbing and anti-corrosion coating of the present invention is specifically as follows: First, 0.9g of BN powder was ultrasonically dispersed in a mixed solution of 10mL of anhydrous ethanol and 20mL of deionized water to obtain a BN suspension, and then 1g of FeSO4·7H2O and 0.4g of FeCl3·6 H2O were added thereto, stirred evenly, and NaOH solution was added dropwise until the pH value was 11. The mixed solution was placed in a high-temperature reactor, reacted at 70°C for 1h, and then filtered, washed with water several times, and dried to obtain magnetically modified BN particles (m-BN); Weigh 1.5g chitosan and dissolve it in 30mL deionized water, then add 0.75g m-BN, ultrasonically disperse it evenly, put it into a high-temperature reactor, react at 120℃ for 4h, filter it, wash it three times and dry it to get a black product. Weigh 1g FeCl3·6H2O and dissolve it in a mixed solution of 12mL deionized water and 12mL anhydrous ethanol, add the black product, ultrasonically disperse it for 30min, heat it at 60℃ and stir it for 24h. Then filter the resulting mixture solution by suction, dry it at 60℃ for 6h to get the m-BN@Fe microsphere precursor. Weigh 1g C4H6CoO4·4H2O and dissolve it in a mixed solution of 25mL deionized water and 25mL anhydrous ethanol, add the obtained m-BN@Fe microsphere precursor, ultrasonically disperse it for 30min, heat it at 60℃ and stir it for 24h, filter it, and dry it at 60℃ for 6h to get the m-BN@Fe-Co microsphere precursor; The m-BN@Fe-Co microsphere precursor was placed in an air furnace with a heating rate of 3°C / min and kept at 600°C for 3 h to obtain multi-shell m-BN@Fe-Co microspheres. Add 1g of m-BN@Fe-Co microspheres, 1g of nano-TiO2 and 0.05g of sodium tripolyphosphate to 80mL of deionized water, disperse by ultrasonic for 30min, add dilute hydrochloric acid to adjust the pH to 4, add 0.1g of sodium dodecylbenzene sulfonate, stir at 40℃ for 2h, dry and grind into powder to obtain m-BN@Fe-Co@TiO2 nanospheres; Weigh 4 gm-BN@Fe-Co@TiO2 nanospheres and add them to 10 g epoxy resin. Stir at 600 rpm for 60 min and then ultrasonically disperse for 20 min. Add 0.5 g diaminocyclohexane, stir evenly and apply it on an aluminum plate. After complete curing, an absorbing and anti-corrosion coating is obtained.
[0027] Comparative Example 1 The only difference from Example 3 is that in step 1, BN is not subjected to modification treatment, and BN powder is directly used for subsequent steps.
[0028] Comparative Example 2 The only difference from Example 3 is that in step 2, no further impregnation treatment with C4H6CoO4·4H2O solution is used.
[0029] Comparative Example 3 The only difference from Example 3 is that the modified nano-TiO2 coating is not performed, and the m-BN@Fe-Co@TiO2 nanospheres are directly used for the subsequent steps.
[0030] Table 1 is a comparison of the wave absorption and anti-corrosion performance of the coating in Example 3, the coating in Comparative Example 1, the coating in Comparative Example 2, and the coating in Comparative Example 3.
[0031] Table 1
[0032] As can be seen from Table 1, the absorbing and anti-corrosion coating of Example 3 has the best comprehensive performance. The BN coating of Comparative Example 1 has not been subjected to magnetic modification treatment, and its attenuation ability to electromagnetic waves has decreased. In the coating of Comparative Example 2, C4H6CoO4·4H2O solution was not used for further impregnation treatment, which seriously affected the construction of the multi-shell core-shell structure, further weakened the multiple reflections of electromagnetic waves, and affected the absorbing effect. The coating of Comparative Example 3 was not coated with modified nano-TiO2, which reduced its anti-corrosion effect. In Example 3, the absorbing and anti-corrosion coating uses magnetically modified BN as the core to enhance its interaction with electromagnetic waves. The multi-shell m-BN@Fe-Co microsphere design forms a multi-level barrier, effectively blocks corrosive media, and enriches the attenuation path of electromagnetic waves, achieving multiple scattering effects of electromagnetic waves. The outer layer is coated with high-density modified TiO2 to enhance interface polarization, optimize wave absorption, and further enhance the anti-corrosion effect through its excellent weather resistance and anti-aging properties. Therefore, it has the best comprehensive performance and is better than all comparative examples.
[0033] Figure 1 This is a microscopic schematic diagram of the m-BN@Fe-Co@TiO2 nanospheres prepared by the present invention. Figure 1 It can be seen that high-density TiO2 is uniformly coated on the surface of multi-layer Fe-Co doped carbon shell and magnetically modified BN particle core.
[0034] The present invention can obtain a high-density TiO2-coated microwave-absorbing and anti-corrosion coating having a multi-layer Fe-Co doped carbon shell and a magnetically modified BN particle core. The BN particles enhance their interaction with electromagnetic waves through magnetic modification, and the multi-layer Fe-Co doped carbon shell increases the microwave absorption mechanism and realizes multiple scattering of electromagnetic waves, thereby improving the microwave absorption efficiency. The high-density coating of the outer layer modified nano-TiO2 enhances the interface polarization and optimizes the microwave absorption effect through its unique electronic structure. The multi-shell m-BN@Fe-Co microsphere design forms a multi-level barrier to effectively block corrosive media. The magnetically modified BN enhances the physical strength of the coating and repels corrosive ions, thereby improving the corrosion resistance. The outer layer high-density modified TiO2 enhances chemical stability, and further enhances the anti-corrosion effect through its excellent weather resistance and anti-aging properties. Therefore, the coating has broad application prospects in multiple key fields such as microwave absorption stealth, corrosion protection, and electromagnetic compatibility.
Claims
1. A method for preparing a boron nitride-based multi-shell radar-absorbing and anti-corrosion coating, characterized in that: Specifically, magnetic modified BN is first prepared, then a multi-shell m-BN@Fe-Co microsphere precursor is prepared, and calcined, and then coated with modified nano-TiO2, and finally an absorbing and anti-corrosion coating is prepared.
2. The method for preparing the boron nitride-based multi-shell absorbing and anti-corrosion coating according to claim 1, characterized in that: Follow the steps below to implement it: Step 1: Preparation of magnetically modified BN BN powder was added into a mixed solution of anhydrous ethanol and deionized water, and then FeSO4·7H2O, FeCl3·6 H2O and NaOH solution were added. After reacting in a water bath, the mixture was filtered, washed with water and dried to obtain magnetically modified BN particles. Step 2: Preparation of multi-shell m-BN@Fe-Co microsphere precursor The magnetically modified BN particles obtained in step 1 are added to a water-soluble polymer solution, filtered, washed and dried after hydrothermal treatment, and then dispersed in a FeCl3·6H2O solution, heated and stirred, filtered and dried, and then dispersed in a C4H6CoO4·4H2O solution, heated and stirred, filtered and dried to obtain a multi-shell m-BN@Fe-Co microsphere precursor; Step 3, calcination The multi-shell m-BN@Fe-Co microsphere precursor obtained in step 2 is calcined to obtain multi-shell m-BN@Fe-Co microspheres; Step 4: Modified nano-TiO2 coating The m-BN@Fe-Co microspheres, nano-TiO2 and dispersant obtained in step 3 are dispersed in deionized water, a dilute hydrochloric acid solution is added to adjust the pH, a surfactant is added, and the mixture is heated, stirred, dried and ground to obtain m-BN@Fe-Co@TiO2 nanospheres; Step 5: Prepare the microwave-absorbing and anti-corrosion coating The m-BN@Fe-Co@TiO2 nanospheres obtained in step 4 are mixed with epoxy resin, stirred evenly and then dispersed by ultrasonic, a curing agent is added, stirred evenly and then applied on an aluminum plate, and after being completely cured, a microwave-absorbing and anti-corrosion coating is obtained.
3. The method for preparing the boron nitride-based multi-shell absorbing and anti-corrosion coating according to claim 2, characterized in that: In the step 1, the concentration of BN powder in the mixed solution of anhydrous ethanol and deionized water is 0.03 g / mL to 0.05 g / mL, the volume ratio of anhydrous ethanol to deionized water is 1:2, the mass ratio of FeSO4·7H2O, FeCl3·6H2O and BN is 2:1:3 to 5:1:3, NaOH solution is added until the pH reaches 10 to 12, the water bath temperature is 40°C to 70°C, and the reaction time is 1h to 3h.
4. The method for preparing the boron nitride-based multi-shell absorbing and anti-corrosion coating according to claim 2, characterized in that: In the step 2, the mass ratio of m-BN to the water-soluble polymer is 1:2~2:1, the hydrothermal temperature is 120°C~180°C, the hydrothermal time is 4h~8h, and the water-soluble polymer solution is any one of polyvinyl alcohol, polyacrylic acid, polycarbonate, chitosan, glucose, and polyacrylamide dissolved in deionized water, and its concentration in deionized water is 0.05g / mL~0.1g / mL.
5. The method for preparing the boron nitride-based multi-shell absorbing and anti-corrosion coating according to claim 2, characterized in that: In the step 2, the FeCl3·6H2O solution and the C4H6CoO4·4H2O solution are respectively a mixed solution of FeCl3·6H2O dissolved in deionized water and anhydrous ethanol, and a mixed solution of C4H6CoO4·4H2O dissolved in deionized water and anhydrous ethanol, the concentrations of FeCl3·6H2O and C4H6CoO4·4H2O in the deionized water-anhydrous ethanol mixed solution are both 0.015 g / mL to 0.05 g / mL, the mass ratio of m-BN to FeCl3·6H2O and C4H6CoO4·4H2O is 1:1:1 to 1:2:2, the heating temperature is 40°C to 60°C, the stirring time is 12h to 24h, the drying temperature is 60°C to 80°C, and the drying time is 6h to 12h.
6. The method for preparing the boron nitride-based multi-shell absorbing and anti-corrosion coating according to claim 2, characterized in that: The step 3 is specifically as follows: calcining the multi-shell m-BN@Fe-Co microsphere precursor obtained in step 2 at 400° C. to 600° C. in an air furnace, with a heating rate of 3° C. / min, and keeping the temperature for 1 h to 4 h.
7. The method for preparing the boron nitride-based multi-shell absorbing and anti-corrosion coating according to claim 2, characterized in that: In step 4, the dispersant is any one of sodium pyrophosphate, polyethylene glycol, sodium polyacrylate, and sodium tripolyphosphate; the surfactant is any one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polysorbate 80, and sodium dodecylbenzene sulfonate; the mass ratio of m-BN@Fe-Co microspheres, nano-TiO2, dispersant, and surfactant is 20:20:1:2-20:40:1:2; the concentration of nano-TiO2 in deionized water is 0.005 g / mL-0.015 g / mL; the pH is adjusted to 4-6; and stirring is performed at 40°C-60°C for 2h-4h.
8. The method for preparing the boron nitride-based multi-shell absorbing and anti-corrosion coating according to claim 2, characterized in that: In the step 5, the mass filling rate of m-BN@Fe-Co@TiO2 nanospheres in the epoxy resin is 10%~50%, the curing agent is any one of diethylenetriamine, fatty polyamine ethylenediamine, polyetherdiamine, diaminocyclohexane, and trimethylhexanediamine, and the mass filling rate of the curing agent in the epoxy resin is 2%~5%.
9. The method for preparing the boron nitride-based multi-shell absorbing and anti-corrosion coating according to claim 2, characterized in that: During stirring in step 5, the stirring speed of the stirrer is 600 rpm to 800 rpm, the stirring time is 20 min to 60 min, and the ultrasonic time is 10 min to 30 min.
10. An anti-corrosion coating prepared according to the method for preparing a boron nitride-based multi-shell absorbing anti-corrosion coating according to any one of claims 1 to 9.
Citation Information
Patent Citations
Co-Fe alloy / carbon sphere composite microwave absorbent and preparation method thereof
CN107338024A
Composite wave-absorbing material, electromagnetic shielding film and preparation method of electromagnetic shielding film
CN117143398A
Anionic polymer surface-treated ceramic particle and method thereof
KR1020130076045A
Method for coating ceramic particles with magnetic substances
KR1020140085915A
Cited By
High-temperature-resistant environment-friendly household ceramic and preparation method thereof
CN120441289A